The Book Thief - Markus Zusak (New York Black Swan, 2013)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors. Includes readers' guide.
Keywords: Books and reading; Storytelling; Death; Jews; World War, 1939-1945; English Fiction